آليات تفعيل الاقتصاد الرقمي في تحسين الأداء المؤسسي وزيادة العائد الاقتصادي بوزارة الشباب والرياضة في ضوء رؤية مصر 2030 - سيد، محمود محمد Sayed, Mahmoud Mohammed (جامعة المنيا - كلية التربية الرياضية, 2019)
يستهدف البحث التعرف على آليات تفعيل الاقتصاد الرقمي في تحسين الأداء المؤسسي وزيادة العائد الاقتصادي بوزارة الشباب والرياضة في ضوء رؤية مصر 2030 م، استخدام الباحث المنهج الوصفي "أسلوب المسح". يتمثل مجتمع البحث في العاملين بالإدارات المركزية بوزارة الشباب والرياضة، والبالغ عددهم (977) فردا، وقام الباحث باختيار العينة بالطريقة الطبقية العشوائية من الإدارات قوامها (250) فردا، بنسبة مئوية قدرها (25.59%) من مجتمع البحث، استخدم الباحث الاستبيان كأداة لجمع البيانات وقام بتصميم (3) استبيانات. وأشارت أهم النتائج إلى عدم تحقق أنشطة الاقتصاد الرقمي داخل وزارة الشباب والرياضة بما يتعارض مع رؤية مصر 2030، أن مستوى الأداء المؤسسي لم يصل إلى المستوى المرغوب بكونه أعلى جهة لإدارة الرياضة المصرية، تدني مستوى دلالات العائد الاقتصادي داخل الوزارة، توجد علاقة ارتباطية طردية دالة إحصائيا بين الاقتصاد الرقمي وكلا من الأداء المؤسسي والعائد الاقتصادي بوزارة الشباب والرياضية، يسهم الاقتصاد الرقمي في تحسين كلا من الأداء المؤسسي والعائد الاقتصادي بوزارة الشباب والرياضة، التوصل إلى آليات لتفعيل الاقتصاد الرقمي في تحسين الأداء المؤسسي وزيادة العائد الاقتصادي بوزارة الشباب والرياضة في ضوء رؤية مصر 2030. The research aims to identify the mechanisms of activating the digital economy in improving the institutional performance and increasing the economic return of the Ministry of Youth and Sports in light of the vision of Egypt 2030 AD. The researcher uses the descriptive approach "survey method", the research community is represented by the employees in the central departments of the Ministry of Youth and Sports, whose number is (977) individuals The researcher selected the random stratified sample from those departments, consisting of (250) individuals, with a percentage of (25.59%) of the research community. The researcher used the questionnaire as a tool to collect data and designed (3) questionnaires, namely (digital economy, institutional performance, Economic return) at the Ministry. The most important results indicated that digital economy activities within the Ministry had not been achieved in contradiction, that the level of institutional performance in the Ministry did not reach the desired level as it being the highest authority for the Egyptian Sports Administration, the level of indications of the economic return within the Ministry of Youth and Sports has decreased. A statistically significant positive correlation relationship between the digital economy and both the institutional performance and the economic return in the Ministry of of Youth and Sports.
Keywords: الاقتصاد الرقمي -- الأداء المؤسسي -- وزارة الشباب والرياضة -- العوائد الاقتصادية -- مصر